Implementasi Akuntansi Pertanggungjawaban sebagai Pengendalian Biaya di Perusahaan Jasa Ketenagalistrikan di Jawa Tengah - Ani Setyowati; Guruh Mulia Widayat; Novianto Noegroho (Universitas Katolik Soegijapranata, Semarang, 2023)
This research aims to explore responsibility accounting as a tool used to control financial results in companies. Cost control as an element of accountability accounting is believed to be an important strategy in holding leaders accountable for their performance in the company. The focus of the research was carried out at service companies operating in the electricity sector. The findings show that service companies as companies that prioritize customer satisfaction still need control in the field of financing to increase profitability as an accountability for the performance of managers in the company